Anticoagulation in venovenous extracorporeal membrane oxygenation - Jung, Carolin; Stueber, Thomas; Mirus, Martin; Heubner, Lars; Spieth, Peter Markus (Frontiers in Medicine, 2025)
Venovenous extracorporeal membrane oxygenation (VV-ECMO) is a lifesaving therapy in severe acute respiratory distress syndrome (ARDS). Unfortunately, bleeding and thrombotic complications occur regularly due to coagulation disorders associated with the device, the underlying disease, and the anticoagulation management. To facilitate a personalized approach to hemostasis in individuals receiving ECMO support, it is essential to assess the coagulative state of the patient while simultaneously taking into account the underlying medical condition and administered therapies.